Special exercises using tools and their effect on learning the skill of landing with Salto backward tucked to stand on the horizontal bar - Akbar, Roaa; Yassin , Shaima; hamza , Jamal (Journal of Physical Education, 2024)
Special exercises in individual games are an important pillar in learning their basic skills. The aim of the research is to prepare special exercises using tools and their effect on learning the skill of landing with Salto backward tucked to stand - knowing the effect of special exercises using tools and their effect on learning the skill of landing with Salto backward tucked to stand on the horizontal bar. Either the research assumes the existence of significant differences in the pre- and post-tests in learning the skill of landing with Salto backward tucked to stand on the horizontal bar in favor of the post-test. The researchers used the experimental method with a single sample design to suit the research problem, as the research community was determined by (12) players affiliated with the Baghdad Governorate Gymnastics Training Center and affiliated with the Iraqi Central Gymnastics Federation, and their ages ranged between (9-13) years, and they are the junior category. As for the research sample, the researchers chose (8) players, and the research sample was chosen intentionally and (4) players were excluded from the original research community, while the exploratory sample consisted of (3) players from the research community, and the research sample constituted (66%) of the research community. The exploratory sample (25%) of it. The researchers concluded: Conclusions: Special exercises affected learning and improving the performance of the skill of landing with Salto backward tucked to stand on the horizontal bar for juniors - The use of special tools also had a not insignificant role in learning and improving the performance of the skill of landing with Salto backward tucked to stand. The researchers recommend using special exercises using tools to teach other basic skills on the horizontal bar and other devices.